Asphalt mixture workability and effects of long-term conditioning methods on moisture damage susceptibility and performance of warm mix asphalt. (20th May 2019) - Teh, Sek Yee; Hamzah, Meor Othman
Graphical abstract: Highlights: WMA produced at lower temperatures than HMA exhibited enhanced workability. Specimens subjected to simultaneous LTA and water damage recorded the highest percentage adhesive failure and lowest ITS. Polymer modified binder mixtures demonstrated superior moisture damage resistance than unmodified binder mixtures, regardless of conditioning method. Abstract: The destructive effects of moisture remain to be the main distress adversely influencing pavement performance. Warm mix asphalt (WMA) compacted at lower temperatures than Hot Mix Asphalt (HMA) is more vulnerable to moisture infiltration and subsequent stripping at the asphalt-aggregate interface. To evaluate the potential mechanisms, the failure severity was computed in indirect tension. Two binder types and various compaction temperatures were used for sample fabrications. The gyratory compaction data were used to quantify the mixtures Workability Index (WI) and Compaction Energy Index (CEI). Six long-term conditioning methods were used namely, Long-Term Aged (LTA), Long-Term Aged + 1 Freeze-Thaw (F-T), LTA + 3 F-T, LTA + 1 F-T (Accelerated Laboratory Vacuum Saturation (ALVS)), simultaneous LTA + Moisture-Induced Damage and simultaneous LTA + Water Damage. The ALVS was used to subject asphalt mixtures to the combined effects of pore pressure and high temperature. As aging and moisture damage occur concurrently during the pavement service life, a new moisture conditioning chamber was fabricated to simulate the simultaneous effects of LTA and moisture/water damage. The effects of conditioning on the indirect tensile strength (ITS), fracture energy, resilient modulus and percentage adhesive failure were investigated. The percentage adhesive failure and broken aggregates were quantified using the advanced 3-D imaging technique. WMA compacted at lower temperatures exhibited improved workability in terms of lower CEI and higher WI than HMA. The mixtures percentage adhesive failure increased, while ITS reduced with F-T cycles. Asphalt mixtures subjected to simultaneous LTA and water damage exhibited the highest percentage adhesive failure and lowest ITS compared to other conditioning methods. ALVS conditioned specimens showed slightly higher percentage adhesive failure than LTA + 1 F-T specimens. The test results also demonstrated that polymer modified binder mixtures exhibited superior moisture resistance than unmodified binder mixtures, regardless of compaction temperature and conditioning level.